2014
DOI: 10.1021/om500965k
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Titanocene–Gold Compounds as Potential Chemotherapeutics in Renal Cancer. Study of their Protein Kinase Inhibitory Properties

Abstract: Early–late transition metal TiAu2 compounds [(η-C5H5)2Ti{OC(O)CH2PPh2AuCl}2] (3) and new [(η-C5H5)2Ti{OC(O)-4-C6H4PPh2AuCl}2] (5) were evaluated as potential anticancer agents in vitro against renal and prostate cancer cell lines. The compounds were significantly more effective than monometallic titanocene dichloride and gold(I) [{HOC(O)RPPh2}AuCl] (R = −CH2– 6, −4-C6H4– 7) derivatives in renal cancer cell lines, indicating a synergistic effect of the resulting heterometallic species. The activity on renal can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 68 publications
1
88
1
3
Order By: Relevance
“…Bimetallic or trimetallic molecules such as titanocenes incorporating Ru(II), Pt(II) and Pd(II) centers, 18,19 and a number of derivatives containing ferrocene moieties and other metals 20 were recently described. Heterometallic compounds incorporating gold(I) fragments have been reported for titanocene, 19,21,22 ruthenocene, 23 platinum(II) 24 and rhenium(I) derivatives. 25 Ferrocenyl phosphanes were also incorporated in the iminophosphorane skeleton of gold(III) coordination complexes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bimetallic or trimetallic molecules such as titanocenes incorporating Ru(II), Pt(II) and Pd(II) centers, 18,19 and a number of derivatives containing ferrocene moieties and other metals 20 were recently described. Heterometallic compounds incorporating gold(I) fragments have been reported for titanocene, 19,21,22 ruthenocene, 23 platinum(II) 24 and rhenium(I) derivatives. 25 Ferrocenyl phosphanes were also incorporated in the iminophosphorane skeleton of gold(III) coordination complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the incorporation of gold and of a second metal within the same molecule may offer advantages in their use as potential anticancer derivatives. Improved stability, 2122 solubility 21,22 or lower toxicity in vivo 22 with respect to the individual monometallic fragments, or a beneficial combination of medicinal properties ( e.g. a cell imaging agent plus a cytotoxic agent) 22 were reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results reveal that YM155 is a potentially novel strategy reverse the resistance in RCC. [41] evaluated the potential anticancer activity of the compounds. They found that the organometallic compounds were significantly more effective than monometallic titanocene dichloride and gold(I) [{HOC(O) RPPh2}AuCl] (R = -CH2-6, -4-C6H4-7) derivatives in renal cancer cell lines, suggesting a synergistic function of the resulting heterometallic species.…”
Section: Ym155mentioning
confidence: 99%
“…2 Several new lines of research suggest that gold(I) has a significant potential as a component of therapies designed to inhibit therapeutically relevant targets, such as zinc-finger domains 3 and protein kinases. 4 …”
Section: Introductionmentioning
confidence: 99%